Novel hypophosphite hybrid perovskites of [CH3NH2NH2][Mn(H2POO)3] and [CH3NH2NH2][Mn(H2POO)2.83(HCOO)0.17] exhibiting antiferromagnetic order and red photoluminescence. Issue 32 (19th May 2020) - Mączka, Mirosław; Gągor, Anna; Pikul, Adam; Stefańska, Dagmara
Abstract : The first perovskite-type hypophosphite-linked dense metal–organic framework exhibiting red emission and antiferromagnetic order at 6.5 K. Abstract : Hybrid perovskites based on hypophosphite ligands constitute an emerging family of compounds exhibiting unusual structures and offering a platform for construction of novel functional materials. We report the synthesis, crystal structure, and magnetic and optical properties of novel undoped and HCOO − -doped manganese hypophosphite frameworks templated by methylhydrazinium cations. The undoped compound crystallizes in a three-dimensional perovskite-like orthorhombic structure, space group Pnma, with ordered organic cations located in windows between the perovskite cages expanding along the a -direction. Both conventional anti-phase tilting, unconventional in-phase tilting and columnar shifts in the a -direction are present. Doping with HCOO − ions has a insignificant influence on the crystal structure but leads to a decrease of the unit cell volume. Magnetic studies indicate that these compounds order antiferromagnetically at T N = 6.5 K. Optical studies indicate that they exhibit red photoluminescence under 266 nm excitation with the activation energy for thermal quenching of 98 and 65 meV for the undoped and doped sample, respectively. For the undoped sample, the emission lifetime reaches 5.05 ms at 77 K but it decreases to 62.26 μs at 300 K. The low value of the activation energy and huge temperature dependence of photoluminescence intensity suggest a high potential of these hypophosphites for non-contact temperature sensing.